Kajian Hukum Tentang Faktor-Faktor Yang Mempengaruhi Pembatalan Perjanjian - Atma Bagus Wibowo; Dimas Fian Wahyu Mahardika (JOURNAL SAINS STUDENT RESEARCH, 2023)
This legal study delves into the aspects influencing the annulment of agreements, offering a profound understanding of the legal factors involved in the annulment process. The analysis aims to provide a comprehensive view of the factors that can trigger the annulment of agreements, such as contract violations, non-compliance with agreement terms, or significant changes in conditions. Within the legal framework, this research identifies and evaluates the legal implications of each factor affecting the validity of agreements. Additionally, the study highlights the role of legal jurisdiction and regulations applicable to the annulment process. The research methodology includes the analysis of legal documents, relevant legal cases, and an in-depth literature review. The findings of this research are expected to offer a clear and detailed perspective to legal practitioners, academics, and parties involved in agreements, enabling them to understand and manage risks associated with agreement annulment. The practical implications of this study involve a profound understanding of the legal aspects that need to be considered in agreements, with the goal of enhancing security and sustainability in their execution.